2021
DOI: 10.21608/mjvh.2021.193420
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of NS5B Region of Hepatitis C Virus in Togo

Abstract: Background: Hepatitis C virus (HCV) infection is a major cause of chronic liver disease worldwide. The high prevalence and spread rates of the disease require serious actions to stop these rates. Determination of HCV genotypes and subgenotypes adds significant knowledge about the epidemiology of the disease, and provides and added value in the decision-making process of what strategy to follow and what therapy response to expert. The molecular epidemiology and genetic variability of HCV variant circulating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another study revealed that DNA sequencing on NS5B region was able to precisely detect few HCV subtypes; 1a, 1b, 2a, 3b, 6a, as well as new subtypes; 1b-2a, 1b-2k and 6d-6k (42). NS5B region was successfully sequenced in around 77% of the positive samples reported in the recent study by Anyovi et al (43). Therefore, NS5B region is among the recommended region for HCV genotyping as well as Core due to the highly informative in phylogeny analysis and identification of HCV strains (43).…”
Section: Hcv Genome Organization and Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study revealed that DNA sequencing on NS5B region was able to precisely detect few HCV subtypes; 1a, 1b, 2a, 3b, 6a, as well as new subtypes; 1b-2a, 1b-2k and 6d-6k (42). NS5B region was successfully sequenced in around 77% of the positive samples reported in the recent study by Anyovi et al (43). Therefore, NS5B region is among the recommended region for HCV genotyping as well as Core due to the highly informative in phylogeny analysis and identification of HCV strains (43).…”
Section: Hcv Genome Organization and Functionmentioning
confidence: 93%
“…NS5B region was successfully sequenced in around 77% of the positive samples reported in the recent study by Anyovi et al (43). Therefore, NS5B region is among the recommended region for HCV genotyping as well as Core due to the highly informative in phylogeny analysis and identification of HCV strains (43).…”
Section: Hcv Genome Organization and Functionmentioning
confidence: 99%